Dosing Strategies for Improving the Risk-Benefit Profile of Ponatinib in Patients With Chronic Myeloid Leukemia in Chronic Phase - Castagnetti, Fausto; Pane, Fabrizio; Rosti, Gianantonio; Saglio, Giuseppe; Breccia, Massimo (Frontiers in Oncology, 2021)
The treatment of chronic myeloid leukemia (CML) has been advanced by the development of small-molecule tyrosine kinase inhibitors (TKIs), which target the fusion protein BCR-ABL1 expressed by the Philadelphia chromosome. Ponatinib is a 3rd generation TKI that binds BCR-ABL1 with high affinity and inhibits most BCR-ABL1 mutants, including the T315I mutation. The approved starting dose of ponatinib is 45 mg once daily (full dose), however, the need for a full dose, especially in patients with dose adjustments due to tolerability problems, remains undemonstrated. Lower starting doses of ponatinib (30 mg or 15 mg once daily) for patients “with lesser degrees of resistance or multiple intolerances, especially those with an increased cardiovascular risk profile” has been recommended by the 2020 European LeukemiaNet. However, the available literature and guidance on the use of ponatinib at low dosage are limited. The objective of this paper is to describe how we select ponatinib dosage for CML patients in chronic phase in our clinical practice based on the available evidence and our clinical experience. We propose dosing regimens for the optimal starting dose for six generic cases of CML patients in chronic phase eligible for the switch to ponatinib and provide an algorithm to guide ponatinib dosing during treatment.